Effect of Managerial Overconfidence and Compensation on Share Repurchase: Empirical Evidence from Taiwanese Firms - Tzu-Yu Liu,; Li-Lun Liu,; John Francis Diaz, (Asian Academy of Management Journal of Accounting and Finance, 2016)
This study analyses the effect of managerial overconfidence and compensation on the behaviour of Taiwanese CEOs who execute share repurchase. A panel data of 715 companies listed in Taiwan Stock Exchange Corporation and over-the-counter from 2008 to 2012 are used for the analysis. Results show that the managers who receive short-term performance bonuses and equity incentives tend to repurchase shares, and these bonuses and incentives are increased when the managers overly estimate the prospects of the company. Overconfident managers are also inclined to use additional capital in buying back shares, especially when they are under a profit-sharing scheme and have additional stock option incentives. The research findings are robust and provide strong policy implications, which advise the board of directors to improve their checks and balances, minimise costly managerial decisions, determine the motives of CEOs in implementing share buybacks, and lessen the information asymmetry inside and outside their business organisations. This study also suggests that future research should look into the tendency of Taiwanese managers to select types of financing (i.e., debt, equity, or a mix) or establish business empires through mergers and acquisitions. Other than the private sector, the case of government-owned and -controlled corporations should also be investigated.